Role and Involvement of TENM4 and miR-708 in Breast Cancer Development and Therapy - Giulia Peppino; Federica Riccardo; Maddalena Arigoni; Elisabetta Bolli; Giuseppina Barutello; Federica Cavallo; Elena Quaglino (Cells, 2022)
Teneurin 4 (TENM4) is a transmembrane protein that is codified by the ODZ4 gene and is involved in nervous system development, neurite outgrowth, and neuronal differentiation. In line with its involvement in the nervous system, TENM4 has also been implicated in several mental disorders such as bipolar disorder, schizophrenia, and autism. TENM4 mutations and rearrangements have recently been identified in a number of tumors. This, combined with impaired expression in tumors, suggests that it may potentially be involved in tumorigenesis. Most of the TENM4 mutations that are observed in tumors occur in breast cancer, in which TENM4 plays a role in cells’ migration and stemness. However, the functional role that TENM4 plays in breast cancer still needs to be better evaluated, and further studies are required to better understand the involvement of TENM4 in breast cancer progression. Herein, we review the currently available data for TENM4′s role in breast cancer and propose its use as both a novel target with which to ameliorate patient prognosis and as a potential biomarker. Moreover, we also report data on the tumorigenic role of miR-708 deregulation and the possible use of this miRNA as a novel therapeutic molecule, as miR-708 is spliced out from TENM4 mRNA.